Pengaruh Pengelolaan Keuangan, Literasi Keuangan Dan Permodalan Terhadap Kinerja Keuangan Umkm Di Kota Pekanbaru - Al Putri Oktavia; Liza Ulfiana; Arif Mahasin Sondani (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to determine the influence of financial management, financial literacy, and capital on the financial performance of MSMEs in Pekanbaru City. The sample size was 98 MSMEs registered with the Cooperatives Office from various sectors. The test instruments used were validity and reliability tests, multiple regression, simultaneous tests, and determination tests.